2023
DOI: 10.3389/fpls.2023.1080666
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genetic determination of tuber shape and eye depth in potato natural population based on autotetraploid potato genome

Abstract: Potato is one of the world’s most important food crops, with a time-consuming breeding process. In this study, we performed a genome-wide association (GWAS) analysis of the two important traits of potato tuber shape and eye depth, using the tetraploid potato genome (2n=4x=48) as a reference. A total of 370 potatoes were divided into three subgroups based on the principal component analysis and evolutionary tree analysis. The genetic diversity within subgroups is low (5.18×10-5, 4.36×10-5 and 4.24×10-5). Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The current study reports three QTL-MTAs on chromosome 4 (Table 5 ) and two (chr04_5763134 and chr04_10456693) of these support the chromosome 4 QTL reported by Hara-Skrzypiec et al ( 2018 ). Zhao et al ( 2023 ) found a QTL for eye depth on chromosome 6 (Chr06A2:25.9–26.4 Mb (Wang et al 2022 )) but the same chromosome QTLs (chr06_40734919 and chr06_40735030, Table 5 ) detected here were ~ 14 Mb distance apart. Hara-Skrzypiec et al ( 2018 ) identified another eye depth QTL towards the bottom part of chromosome 11 (44.8 cM; 34.2 Mb, DMv6.01; see above for cM-to-Mb conversion), however, all four QTL-MTAs detected in the current study were on the top part of the same chromosome (Table 5 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The current study reports three QTL-MTAs on chromosome 4 (Table 5 ) and two (chr04_5763134 and chr04_10456693) of these support the chromosome 4 QTL reported by Hara-Skrzypiec et al ( 2018 ). Zhao et al ( 2023 ) found a QTL for eye depth on chromosome 6 (Chr06A2:25.9–26.4 Mb (Wang et al 2022 )) but the same chromosome QTLs (chr06_40734919 and chr06_40735030, Table 5 ) detected here were ~ 14 Mb distance apart. Hara-Skrzypiec et al ( 2018 ) identified another eye depth QTL towards the bottom part of chromosome 11 (44.8 cM; 34.2 Mb, DMv6.01; see above for cM-to-Mb conversion), however, all four QTL-MTAs detected in the current study were on the top part of the same chromosome (Table 5 ).…”
Section: Discussionsupporting
confidence: 64%
“…Tuber eye depth is an important agronomic trait that affects the appearance and processing quality of tubers where potatoes with deep eyes contribute to significant peeling losses and are also not favoured by the consumers. To aid breeding potatoes with shallow eyes and uniform shape, several studies have been conducted in the past to identify genetic factors underlying this trait and identified a major locus controlling eye depth on chromosome 10 including minor effect QTLs on chromosomes 1, 2, 3, 4, 5, 6, 11, and 12 (Hara-Skrzypiec et al 2018 ; Li et al 2005 ; Lindqvist-Kreuze et al 2015 ; Pandey et al 2022 ; Prashar et al 2014 ; Rosyara et al 2016 ; Sharma et al 2018 ; Śliwka et al 2008 ; Totsky et al 2020 ; Zhang et al 2022 ; Zhao et al 2023 ). GWAS here detected the most significant QTL for tuber eye depth on chromosome 10 corroborating the findings from the previous studies, and additional significant QTL-MTAs were revealed on chromosomes 3, 4, 6, 7, 9, 10, 11 and 12 (Table 5 ; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As for other species, several studies have identified SNPs associated with agronomical and quality traits, such as tuber shape, eye depth, and fry color retention during low-temperature storage ( Sharma et al., 2018 ; Byrne et al., 2020 ; Zhang et al., 2022a ; Pandey et al., 2023 ; Zhao et al., 2023 ). Moreover, multiple genetic markers and candidate genes aimed at enhancing disease resistance to late blight have been identified by Wang et al.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%
“…As for other species, several studies have identified SNPs associated with agronomical and quality traits, such as tuber shape, eye depth, and fry color retention during low-temperature storage (Sharma et al, 2018;Byrne et al, 2020;Zhang et al, 2022a;Pandey et al, 2023;Zhao et al, 2023). Moreover, multiple genetic markers and candidate genes aimed at enhancing disease resistance to late blight have been identified by Wang et al (2021) and Sood et al (2023), while Dıáz et al (2021) and Alvarez-Morezuelas et al ( 2023) investigated plant's response to abiotic stressors, revealing genes and QTLs that may aid in developing varieties better suited to changing environmental conditions and drought seasons.…”
Section: Potatomentioning
confidence: 99%